Advanced ANSI SQL data modeling and structure processing - David, Michael M. (Artech House computer science library., 1999)
"Here's an essential tool for utilizing the ANSI SQL outer join operation to perform simple or complex data modeling. Inside, you get a comprehensive review of the outer join operation, its powerful syntax, and new features and capabilities that can be developed based on the operation's data modeling capacity."--Jacket